PEMANFAATAN LIMBAH PLASTIK SEBAGAI BAHAN BETON RINGAN RAMAH LINGKUNGAN - Nadia Meilani; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to examine the effect of utilizing plastic waste as an additive material in lightweight concrete on the compressive strength of the concrete. The testing was conducted with variations in the percentage of plastic waste at 5%, 10%, and 15% in the concrete mix, then compared to normal concrete without plastic waste. The results showed that the highest compressive strength was obtained in the mix with 5% plastic waste, reaching 29.09 MPa, which is slightly higher than the normal concrete with a compressive strength of 28.24 MPa at 28 days of age. At 10% and 15% plastic waste, the compressive strengths were 28.45 MPa and 28.03 MPa respectively, indicating a decrease compared to the 5% mix. These data suggest that the addition of plastic waste does not consistently improve the quality of concrete, so the optimal percentage must be carefully determined to avoid reducing the concrete’s strength. This study illustrates that the utilization of plastic waste as an additive in lightweight concrete can enhance compressive strength at certain levels, but excessive use may negatively affect the concrete’s performance.Keywords: Plastic Waste, Environmentally Friendly Lightweight Concrete